the prevalence of accommodative spasm in adults - العاشور, باسل; تيم درويش; محمود رجب (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: Determining the prevalence of accommodative spasm in adults Methods: 200 patients (400 eyes) participated in the study, a detailed medical history was taken and information of age and sex was recorded. After informed consent was obtained, a comprehensive ophthalmological examination was performed, including examination of visual acuity, corrected visual acuity, measurement of refraction by Autorefractor, in addition to examination using slit lamp for the anterior sections of the eye and the poseterior sections of the eye. Cyclopentolate 1% was instilled into both eyes 3 times with an interval of 10 minutes, and refraction was measured after 20 minutes from the third time with an Autorefractor device. Results: It was found that 19% of the included patients had accommodative spasm, and we found statistically significant differences regarding the occurrence of accommodative spasm and gender, the incidence of accommodative spasm was higher in the female group, and we did not find a staticlically significant relationship between smoking and accommodative spasm, while there was a significant relationship Statisticallybetween the occurrence of accommodative spasm and age, as the cases who had accommodative spasm were younger. Conclusion: As a result of the natural of modern life and the use of electronic devices, the spread of accommodative spasm can be observed, especially among women and young people. Keywords: refractometer, cycloplegia, accommodative spasm